First-principles calculations of chromium oxide containing impurities - Rivera Escobar, R. (2014)
First-principles calculations based on the Density Functional Theory (DFT) within the Generalized Gradient Approximation (GGA) have been used to study the defective alpha-Cr2O3 crystal. Structural, electronic and magnetic properties due to Ti, Ca and N impurities have been studied. Ti-doped supercell shows that the nature of chemical bonding in the neighbourhood of the impurity turns into more ionic one. The atoms situated close to the defect have a trend to move away from the Ti imperfection. Additionally, a metallic state has been observed implying the n-type conductivity. Ca-doped crystal shows atomic shifts in the vicinity of defect, and no local energy level within the band-gap has been observed. Microstructure in the N-doped crystal is such as some atoms move towards the impurity whereas the rest of them move outwards. The band-gap shrinkage has been found. Finally, there are notable changes upon the magnetic properties of doped alpha-Cr 2O3 crystals implying that it might not act as an antiferromagnetic substance.